Constraint on the equation of state parameter (ω) in non-minimally coupled f(Q) gravity - Sanjay Mandal (Elsevier, 2021)
We study observational constraints on the modified symmetric teleparallel gravity, the non-metricity f(Q) gravity, which reproduces background expansion of the universe. For this purpose, we use Hubble measurements, Baryonic Acoustic Oscillations (BAO), 1048 Pantheon supernovae type Ia data sample which integrate SuperNova Legacy Survey (SNLS), Sloan Digital Sky Survey (SDSS), Hubble Space Telescope (HST) survey, Panoramic Survey Telescope and Rapid Response System (Pan-STARRS1). We confront our cosmological model against observational samples to set constraints on the parameters using Markov Chain Monte Carlo (MCMC) methods. We find the equation of state parameter ω=−0.853−0.020+0.015 and ω=−0.796−0.074+0.049 for Hubble and Pantheon samples, respectively. As a result, the f(Q) model shows the quintessence behavior and deviates from ΛCDM.